2020
DOI: 10.1177/2045125320981500
|View full text |Cite
|
Sign up to set email alerts
|

Stable patients with schizophrenia switched to paliperidone palmitate 3-monthly formulation in a naturalistic setting: impact of patient age and disease duration on outcomes

Abstract: Background: Paliperidone palmitate 3-monthly (PP3M) is a second-generation, long-acting injectable antipsychotic formulation indicated for the maintenance treatment of adults with schizophrenia first stabilized with paliperidone palmitate 1-monthly (PP1M). This exploratory post hoc subgroup analysis of the 52-week, phase 3b REMISSIO study analysed outcomes according to patient age and disease duration in a naturalistic clinical setting. Methods: Outcomes of patients with schizophrenia were analysed according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with other naturalistic studies affirming PP3M is highly effective in relapse prevention and reducing hospital admissions [27,28]. One recent study reports better outcomes for younger patients and suggests that earlier implementation of PP3M in therapy is critical for better long term outcomes and symptomatic remission [29]. Our findings on the effect of age on outcome are consistent with this study.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…Our findings are consistent with other naturalistic studies affirming PP3M is highly effective in relapse prevention and reducing hospital admissions [27,28]. One recent study reports better outcomes for younger patients and suggests that earlier implementation of PP3M in therapy is critical for better long term outcomes and symptomatic remission [29]. Our findings on the effect of age on outcome are consistent with this study.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…In this sense, within our study, patients receiving PP1M and PP3M were older than those receiving AM, suggesting that clinicians may be inclined to prescribe PP1M or PP3M in patients with a longer disease course. However, a recent study reported that PP3M is effective in achieving symptomatic remission both in younger patients (age < 35 years) and in patients newly diagnosed with schizophrenia (< 3 years) [ 42 ]. Further studies are needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the proportion of patients who suffered a side effect leading to treatment discontinuation was similar in all groups. 79 …”
Section: Resultsmentioning
confidence: 99%